Akumulasi Modal Manusia, Pemanfaatan Remitan dan Kendala Pemanfaatannya dalam Peningkatan Kesejahteraan Rumah Tangga Migran kembali di Kabupaten Cilacap - Suyanto Suyanto; Fajrul Falah (Universitas Andalas, 2022)
Return migrants in some areas of migrant’s enclave in Indonesia a have high dependence on work abroad because when they return to Indonesia many no longer have a steady source of income. This happens because they are generally consumptive, spend a lot of money, are glamourous, are less calculating, not have a job plan after not being a migrant. For this reason, the use of remittances migrants is again interesting to study. The aims of this research are to explain the utilization of remittances and the obstacle experienced in the utilization of remittances in improving the welfare of households. The design of this study was a survey and case study. Data collection uses observation, structured interview, in-depth interviews, and FGD. Data analysis uses descriptive statistics and followed by qualitative descriptive and categorical analysis. The result of the research shows that remittances are generally for buying land and building houses, furniture and modern kitchen equipment, motorbikes or cars, and wedding parties, and a small portion is allocated for productive businesses. An obstacle of returning migrants in improving their welfare household is low education, the use of more remittances for consumer goods and investment, and the use of remittances more determined by husbands.